2013
DOI: 10.1136/annrheumdis-2012-eular.3127
|View full text |Cite
|
Sign up to set email alerts
|

SAT0180 B7-H4 expression of renal tubular epithelial cells in patients with lupus nephritis

Abstract: Background B7-H4 is a newly identified B7 family negative co-stimulate molecule, the expression and function of B7-H4, in the pathogenesis of lupus nephritis (LN) is still unclear. Objectives To investigate the expression of B7-H4 in patients with LN and the function of renal tubular epithelial cells (TECs)-associated B7-H4 in the regulation of T cell activation in vitro. Methods 90 LN patients, 3 acute kidney injury patients and 20 healthy donors were referred. Disease activity was assessed by SLEDAI scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…B7-H4-deficient mice in a BALB/c background mounted slightly enhanced T-helper type 1T cell responses and displayed mildly lowered parasite burdens upon Leishmania infection compared to wild-type mice, suggesting a B7-H4 has an inhibitory, albeit mild, effect on Th1 responses ( 54 ). Others have also reported that the soluble B7-H4 in serum of lupus nephritis patients was strongly associated with serum creatinine levels ( 55 ), suggesting a possible correction between SLE and B7-H4 signal pathway.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…B7-H4-deficient mice in a BALB/c background mounted slightly enhanced T-helper type 1T cell responses and displayed mildly lowered parasite burdens upon Leishmania infection compared to wild-type mice, suggesting a B7-H4 has an inhibitory, albeit mild, effect on Th1 responses ( 54 ). Others have also reported that the soluble B7-H4 in serum of lupus nephritis patients was strongly associated with serum creatinine levels ( 55 ), suggesting a possible correction between SLE and B7-H4 signal pathway.…”
Section: Introductionmentioning
confidence: 96%
“…Upregulation of B7-H4 on APCs by IL-10 secreted by Tregs has been proposed as a potential inhibitory mechanism of regulatory T cells ( 44 ). B7-H4 Ig also can alleviate the disease of CIA ( 53 ) and moderate MOG ( 35 55 )/CFA-induced EAE in C57BL/6 mice ( 57 ). However, the role of B7-H4 in SLE has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%